Influence of weed-control measures on weed growth, nutrient uptake and tuber yield of potato (Solanum tuberosum) - Prasad, K; Singh, R S (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted at Ranchi during winter season of 1988-89 and 1989- 90 to study the effect of weed control on weed growth, nutrient uptake by weeds and the crop, and on yield of potato (Solanum tuberosum L.). Cultural weed management (weeding at 30 days after planting followed by earthing-up) was comparable with the pre-emergence application of atrazine @ 1 kg/ha in reducing dry weight of weeds. Atrazine @ 1 kg/ha pre-emergence and fluchloralin@ 1.5 kg/ha pre-plant incorporation proved as good as cultural weed management in reducing nutrient depletion by weeds and in increasing the nutrient uptake by potato at 90 days after planting. Weeding at 30 days after planting + earlhing-up gave the highest tuber yield (25.3 tonnes/ha), which was on a par with that obtained with atrazine @ 1 kg/ha pre-emergence (23.6 tonnes/ha) and pre-plant incorporated fluchloralin @ 1.5 kg/ha (21.7 tonnes/ha). Weed-control efficiency of most of the herbicides was 61--83% compared with 87.5% under cultural weed management.